VD_FINDINFO HC / 2009 / 477 vom 26. November 2009 - VD Tribunal cantonal (2009)
DROIT DES SUCCESSIONS, COMPÉTENCE RATIONE LOCI, CONVENTION DE PARTAGE | 634 CC, 444 al. 1 ch. 1 CPC, 57 al. 1 CPC, 57 al. 2 CPC, 57 CPC, 58 al. 1 CPC, 18 al. 1 LFors, 18 LFors